(untitled) (Al-Aasar, 2025)
Migration is not merely the act of crossing borders; it is an ongoing human struggle for safety, connection, and the hope of rebuilding a life amid the shadows of war and displacement. This article critically examines Silence Is a Sense by Layla AlAmmar, positioning the narrative as a powerful reflection of the contradictions within Western humanitarian discourse in the twenty-first century. Through the unnamed protagonist “Voiceless,” AlAmmar maps the psychological terrain of exile, showing how trauma, violence, and resistance come to define the migrant’s evolving sense of self. Drawing on Michel Foucault’s theories of power, surveillance, and control (Foucault, 1979), and Stuart Hall’s concept of cultural identity (Hall, 1996) the study investigates how migrants are politicized, racialized, and rendered both hyper-visible and unheard by the societies in which they seek refuge. Voiceless’s experiences reveal how host communities exert control—both overt and covert—over migrant bodies and minds. This article contends that migration is not a static condition but a dynamic process shaped by rupture, memory, and cultural dissonance. The protagonist’s attempt to make sense of her trauma underscores the reality that reconciliation is not linear, but an enduring confrontation with power, loss, and the persistent will to exist. Ultimately, the study foregrounds the migrant not as a threat, but as a figure of endurance and resistance within a fractured global order.